Are Hungarian financial markets liquid enough? The theory and practice of FX and government securities market liquidity - Csaba Csávás; Szilárd Erhart (Magyar Nemzeti Bank, 2005)
The subject of our study is market liquidity, which is an important element of the functioning of financial markets. Adequate liquidity of markets is of great significance from the point of view of both market participants and the central bank. On the one hand, of all market segments an examination was made of the domestic forint-euro spot FX market, which is of key importance due to the openness of the country's economy. On the other hand, an analysis was made of the market of forint denominated government bonds, which plays a crucial role in the transmission of the central bank's interest rate policy. [...]
Keywords: F31; G14; G15; 330; market liquidity; financial markets; bid-ask spread; market turnover; Finanzmarkt; Marktliquidität; Spotmarkt; Öffentliche Anleihe; Geld-Brief-Spanne; Ungarn